2011
DOI: 10.1074/jbc.m110.144097
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glyoxalase-I Reduces Hyperglycemia-induced Levels of Advanced Glycation End Products and Oxidative Stress in Diabetic Rats

Abstract: The reactive advanced glycation end product (AGE) precursor methylglyoxal (MGO) and MGO-derived AGEs are associated with diabetic vascular complications and also with an increase in oxidative stress. Glyoxalase-I (GLO-I) transgenic rats were used to explore whether overexpression of this MGO detoxifying enzyme reduces levels of AGEs and oxidative stress in a rat model of diabetes. Rats were made diabetic with streptozotocin, and after 12 weeks, plasma and multiple tissues were isolated for analysis of AGEs, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
143
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(154 citation statements)
references
References 35 publications
10
143
1
Order By: Relevance
“…This decrease in vascular tissue levels of MGO and GO-derived AGEs demonstrates the efficiency of Glo1 overexpression in the detoxification of both GO and MGO. This is in accordance with our previous study in which we demonstrated that Glo1 overexpression prevents elevated blood levels of GO and MGO, and thereby decreases plasma AGE levels after 12 weeks of diabetes [13]. In contrast, the CML levels in the plasma could not be significantly decreased by Glo1 overexpression after 24 weeks of diabetes, suggesting that an excessive formation of CML via additional pathways, like lipid peroxidation, possibly exceeds the detoxification rate in this prolonged state of diabetes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This decrease in vascular tissue levels of MGO and GO-derived AGEs demonstrates the efficiency of Glo1 overexpression in the detoxification of both GO and MGO. This is in accordance with our previous study in which we demonstrated that Glo1 overexpression prevents elevated blood levels of GO and MGO, and thereby decreases plasma AGE levels after 12 weeks of diabetes [13]. In contrast, the CML levels in the plasma could not be significantly decreased by Glo1 overexpression after 24 weeks of diabetes, suggesting that an excessive formation of CML via additional pathways, like lipid peroxidation, possibly exceeds the detoxification rate in this prolonged state of diabetes.…”
Section: Discussionsupporting
confidence: 79%
“…Animal model Heterozygous transgenic Glo1-overexpressing rats were crossed with wild-type Wistar rats (Nippon Seibutsu Zairyo Center, Saitama, Japan) to obtain enough Glo1 -overexpressing progeny for the experiment [13]. Young adult wild-type and Glo1 transgenic male rats (10 weeks of age) were rendered diabetic for a period of 24 weeks by a single intravenous injection of STZ (Sigma-Aldrich, Zwijndrecht, the Netherlands; 45 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GLO1-overexpressing rats were crossed with wild-type (WT) Wistar rats to obtain enough GLO1 progeny for the experiment. The rats were obtained from the Nippon Seibutsu Zairyo Center (Saitama, Japan) and studies using these animals have been recently published [19,20]. All animal studies were carried out in accordance with the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…This was accompanied by protection against high glucose-mediated dysfunction [17,18]. Overexpression of GLO1 in diabetic rats has been shown to be protective against AGE formation and oxidative stress in muscle [19], and also prevent abnormalities in endothelium-dependent vasorelaxation [20]. Likewise, regulation of GLO1 activity in cells can prevent diabetes-related cell dysfunction [21,22].…”
Section: Introductionmentioning
confidence: 99%